The Serendipitous Value of Soil Fauna in Ecosystem Functioning: The Unexplained Explained - Briones, Maria J. I. (Frontiers in Environmental Science, 2018)
Soil fauna is crucial to soil formation, litter decomposition, nutrient cycling, biotic regulation and for promoting plant growth. Yet soil organisms remain underrepresented in soil processes and in existing modelling exercises. This is a consequence of assuming that much of the below-ground diversity is just ecologically “redundant” and that soil food webs exhibit a higher degree of omnivory. However, evidence is mounting accumulating on the strong influence of abiotic filters (temperature, moisture, soil pH) and soil habitat characteristics in controlling their spatial and temporal patterns. From this, new emerging concepts such as “hot moments”, “biological accessabilityaccessibility” and “trophic cascades” have been coined to enable plausible explanations of the observed faunal responses to environmental changes. Here, I argue that many of these findings are indeed “happy accidents” (i.e. “eureka discoveries”) that remain disjointed between disciplines, impeding us from making significant breakthroughs. Therefore, here I provide some new perspectives on soil fauna research and highlight some experimental approaches that ato better explore the great variety of organisms living in soils and their complex interactions. A more comprehensive and dynamic holistic approach is needed to couple soil pedological and biological processes and to combine current experimental and theoretical knowledge if we aim to improve our predictive capacities in determining the persistence of soil organic matter and soil ecosystem functioning.